Facial injuries in Iranian veterans during the Iraq–Iran war (1980–88): differences from recent conflicts. Issue 10 (December 2015) - Khosravi, M.H.; Akhavan, A.
Abstract: Our aim was to identify the pattern and mechanism of facial injuries in Iranian veterans during the Iraq–Iran war and to assess the effectiveness of current protective equipment by retrospectively evaluating 100 Iranian veterans of that war. We randomly included veterans with injuries to various parts of the face, with or without injuries to other organs. None died. We recorded anatomical distribution, incidence, and mechanism of injury as well as injury scores using common references scales. Data are expressed as mean (SD) or number. Fragmentation injuries were the most common ( n  = 40) followed by blast ( n  = 37), shock wave ( n  = 18), and gunshots ( n  = 5). Thirty-five patients had mandibular fractures with a mean (SD) score of 3.7 (1.4). Fifteen patients had injuries to the upper face and 79 to the midface. Twenty-four patients had facial lacerations more than 10 cm long, with a mean facial injury score of 2.4 (2.0). Nineteen had ocular injuries with a mean (SD) ocular trauma score of 64.9 (12.9). Despite recent developments in protective equipment we have seen no significant reduction in the incidence of facial injuries in battle, which could indicate that we need better facial support equipment and more effective education in its use. However, using protective equipment such as goggles and a mandibular protector is highly recommended.